THE ROLE OF ARTIFICIAL INTELLIGENCE IN MANAGEMENT WITHIN THE DIGITAL ECONOMY (Eureka Journal of Humanities and Social Research, 2026)
The rapid development of the digital economy has significantly transformed modern management systems and business processes. In this context, artificial intelligence technologies are becoming one of the main tools for improving managerial efficiency, accelerating decision-making, and increasing organizational competitiveness. This article examines the role of artificial intelligence in management within the digital economy, as well as its impact on strategic planning, data analysis, human resource management, and operational processes. The study also highlights the advantages and challenges associated with the implementation of AI technologies in organizations. The findings indicate that artificial intelligence not only optimizes management activities but also contributes to innovation, productivity growth, and sustainable economic development in the digital era.